SEJARAH EKSPLOITASI MINYAK MINAS PADA TAHUN 1938-1963 - Mardiansyah Pratama Putra; Marwoto Saiman; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Indonesia is one country that is rich in natural resources one of which is petroleum, the oil sector is never apart from the polemic in many countries including Indonesia, which is a country that has oil reserves are abundant, but occurring oil reserves are actually in the